Lifestyle habits and type 2 diabetes traits in patients from healthcare centers in Dubai, United Arab Emirates: a cross-sectional study - Hatab, Kenana; Serdarevic, Fadila; Yousuf, Aisha; Al Ali, Sarah; Al Hajaj, Khawla Eissa Ahmed M.; Almarzooqi, Fatima Mohamed Abdulla Mohamed; Swaidan, Leena Tawfiq; ElHassan, Elsheikh Farah; Kazim, Mahra Nooruddin Abdulwahid; Abdalla, Hanan Hamza Ahmed; Al-Muhaureq, Hanan Ali; Thabit, Salah Mohammed; et al. (Frontiers in Endocrinology, 2025)
ObjectivesGiven the increasing prevalence of type 2 diabetes (T2D) in the United Arab Emirates (UAE), in this cross-sectional study we analyzed the dietary habits, physical activity, as well as anthropometric, clinical, and laboratory parameters in patients with T2D and nondiabetic (ND) subjects from the UAE.Subjects and MethodsThis study included 344 UAE nationals, age 18 or older, who completed a questionnaire to assess their dietary habits and physical activity. The mean age of the recruited participants was 50.9 years (+/-14.1) and females presented 63.4% of the sample size. The linear regression analysis was applied to analyze all clinical parameters and dietary habits as outcomes, while a logistic regression analysis was used to determine the association of patient status with physical activity, as an outcome. All models were controlled for age, gender, and BMI.ResultsThere was a difference in dietary habits between the groups (B=-3.7; CI -6.42, -0.92; p=0.009), where patients with T2D had a lower dietary score than ND subjects, indicating a healthier diet. Our results showed that 19% of T2D patients and 32% of nondiabetic individuals were concerned about their weight. Both groups considered dietary changes important, and more than 90% of participants expressed high or moderate confidence in making those changes. Furthermore, the male nondiabetic subjects demonstrated a 4 times higher level of physical activity versus their diabetic counterparts (OR=4.01, CI: 1.01, 15.9, p=0.04), while the difference in physical activity between female subjects with and without T2D was not demonstrated.ConclusionsOur results showed that patients with T2D consumed a healthier diet than nondiabetic subjects, probably resulting in more favorable total cholesterol and LDL-cholesterol profiles. A gender difference in physical activity was also observed in this sample of UAE population. Our findings suggest that although patients with T2D in the UAE may adopt healthier dietary habits, there remains a significant need to address physical activity disparities, particularly among women, to improve overall health outcomes in this population. Addressing these habits through targeted clinical interventions and lifestyle medicine approach can optimize long-term management and prevention strategies for type 2 diabetes in this region.